Effects of Seasonal Runoff Change on Eco-environmental Water Demand of Qingshui River Channel - Li Xuefeng; Yin Juan; Qiu Xiaocong (Shuitu baochi tongbao)
[Objective] Estimation of the eco-environmental water demand of the Qingshui River channel was carried out in order to provide a basis for ensuring normal ecological functioning and rational allocation of water resources in the basin. [Methods] The eco-environmental water demand of different sections of the main stream of the Qingshui River channel was calculated based on water consumption and an analysis of multi-year hydrological statistics. The seasonal variation characteristics of runoff along with precipitation time and the multi-year hydrological characteristics were considered in the context of ecological water security. With respect to the requirements of different ecological functions of rivers, the Tennant method, area quota method and 90% guarantee rate minimum monthly water demand method were used to calculate the basic ecological water demand, evaporation water demand, sediment transport water demand, and water self-purification water demand. [Results] The eco-environmental water demand of the Qingshui River channel included basic ecological water demand, evaporation water demand, sediment transport water demand, and self-purification water demand. The total annual water demand was 6.29×106 m3 for the upper reaches of the river, 6.57×107 m3 for the middle reaches, and 1.65×108 m3 for the lower reaches. [Conclusion] The eco-environmental water demand of the Qingshui River channel was directly related to sediment content and water quality, and high sediment content was the main factor for the high eco-environmental water demand of Qingshui River channel.